2021
DOI: 10.3390/cells10123472
|View full text |Cite|
|
Sign up to set email alerts
|

Long-Term Treatment with Atypical Antipsychotic Iloperidone Modulates Cytochrome P450 2D (CYP2D) Expression and Activity in the Liver and Brain via Different Mechanisms

Abstract: CYP2D enzymes engage in the synthesis of endogenous neuroactive substances (dopamine, serotonin) and in the metabolism of neurosteroids. The present work investigates the effect of iloperidone on CYP2D enzyme expression and activity in rat brains and livers. Iloperidone exerted a weak direct inhibitory effect on CYP2D activity in vitro in the liver and brain microsomes (Ki = 11.5 μM and Ki = 462 μM, respectively). However, a two-week treatment with iloperidone (1 mg/kg ip.) produced a significant decrease in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 74 publications
1
7
0
Order By: Relevance
“…On the other hand, CP-101,606 diminished the CYP2D activity/protein level in the hypothalamus and striatum, and showed such a tendency in the substantia nigra after 3-week treatment. Thus, the above results show an influence of CP-101,606 on the regulation of brain CYP2D (i.e., CYP2D4, the main rat brain CYP2D enzyme), which usually proceeds at a post-transcriptional level, as indicated by previous pharmacological investigations concerning antipsychotic drugs or nicotine [ 25 , 26 , 27 , 46 ].…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…On the other hand, CP-101,606 diminished the CYP2D activity/protein level in the hypothalamus and striatum, and showed such a tendency in the substantia nigra after 3-week treatment. Thus, the above results show an influence of CP-101,606 on the regulation of brain CYP2D (i.e., CYP2D4, the main rat brain CYP2D enzyme), which usually proceeds at a post-transcriptional level, as indicated by previous pharmacological investigations concerning antipsychotic drugs or nicotine [ 25 , 26 , 27 , 46 ].…”
Section: Discussionsupporting
confidence: 65%
“…It seems, therefore, that differences in intracellular neurotransmitter signaling, availability of endogenous and exogenous active substances dependent on the blood–brain barrier (BBB) permeability and levels of transcription factors between neural and hepatic cells lead to differentiated expression of cytochrome P450 and its susceptibility to regulation at transcriptional or post-transcriptional level in the brain (or brain structures) and the liver. Brain CYP2Ds are usually regulated by xenobiotics at the post-transcriptional level in contrast to the liver enzyme, as shown for some psychotropic drugs and nicotine [ 3 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that lurasidone did not produce any changes in the expression and activity of liver CYP2D (in particular CYP2D4), while it did in the region-dependent manner in the brain (where CYP2D4 is the main CYP2D enzyme), implies that the neuroleptic exerted its effect on the brain enzyme via acting at monoaminergic receptors, and all the more so as similar effects on brain CYP2D in the frontal cortex and nigrostriatal pathway were observed for the atypical neuroleptics previously studied by us, namely, iloperidone and asenapine, which share with lurasidone similar receptor mechanisms in the brain [ 15 , 16 ]. These three atypical neuroleptics act at different types/subtypes of dopaminergic, serotonergic, or noradrenergic receptors ( Table 2 ), which are heterogeneously distributed throughout the brain in different structures and on different types of neuronal and glial cells.…”
Section: Discussionmentioning
confidence: 92%
“…Our earlier studies with other atypical drugs, asenapine and iloperidone, showed that chronic neuroleptic treatment produced drug- and brain region-dependent effects on CYP2D protein level and activity in the brain [ 15 , 16 ], some of which were common. Recent in vitro results with pooled human liver microsomes and microsomes from baculovirus-infected insect cells expressing human CYPs (Supersomes) showed a low potency of lurasidone to inhibit the activity of CYP2D6 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%